SMALL REPRODUCTIVE ORGANS, a SUPERMAN‐like transcription factor, regulates stamen and pistil growth in rice. Issue 4 (30th November 2021) - Xu, Wei; Zhu, Wanwan; Yang, Liu; Liang, Wanqi; Li, Hui; Yang, Li; Chen, Mingjiao; Luo, Zhijing; Huang, Guoqiang; Duan, Lei; Dreni, Ludovico; Zhang, Dabing
Summary: Organ size is determined mainly by cell division and cell expansion. Several genetic factors regulating development of plant lateral organs have been characterized, but those involved in determining reproductive organ size and separation in rice ( Oryza sativa ) remain unknown. We have isolated the rice gene SMALL REPRODUCTIVE ORGANS ( SRO ) encoding a nucleus‐localized Cys2His2 (C2 H2 ) zinc finger protein orthologous to Arabidopsis transcription factor (TF) SUPERMAN (SUP). Combined developmental, genetic, histological and transcriptomic analyses were used to determine the function of SRO in regulating reproductive organ size. SRO affects genes involved in cell division, cell expansion and phytohormone signalling in the rice flower. SRO is specifically expressed in the first stages of stamen filament development to regulate their correct formation and separation. In addition, SRO noncell‐autonomously regulates the size and functionality of male and female reproductive organs. The B‐class MADS‐box gene OsMADS16 / SPW1 is epistatic to SRO, whereas SRO regulates reproductive organ specification and floral meristem determinacy synergistically with C‐class genes OsMADS3 and OsMADS58 . These findings provide insights into how an evolutionarily conserved TF has a pivotal role in reproductive organ development in core eudicots and monocots, through partially conserved expression, function and regulatory network.